Functional models for almost periodic Jacobi matrices and the Toda hierarchy - Vinnikov, V.; Yuditskii, P. (Математическая физика, анализ, геометрия, 2002)
We construct and solve a class of evolution equations for (almost periodic) Jacobi matrices which contains as a special case the well known Todahierarchy. Our construction arises naturally within the framework of functional models on a Riemann surface for almost periodic Jacobi matrices.